Scientiﬁc activity of librarians - part of the university science (Confluenţe Bibliologice, 2026)
In 2012 the University Library's employees, (about 77% from them are holders of the ranks) organized 3 conferences, 4 workshops for school, high school colleges librarians for 16 districts from North of Moldova and and mun. Balti, 11 seminars and public lectures, have participate to 40 professional meetings with 102 communications, published 56 works (including 27 electronic and 14 promotional materials), 104 articles promoting the proper image, creativity and resourcefulness of most loyal employees.
Keywords: information and research activity; scientiﬁc research; bibliographers